a Study on Model in Teaching English at Senior High School in Toraja Utara (Jurnal Keguruan dan Ilmu Pendidikan, 2018)
The objectives of the research is to find out teaching model are used by the English Teachers at Toraja Utara. The researcher employed qualitative method for the study. The data resources for the research were three English teachers, they chose in randomly and the instrument for the research consisted of observation. In analyzing the data, the researcher employed descriptive method. The result showed that, there are five models teaching that used by the English Teachers in teaching English in Toraja Utara. They are: (1) expert (2) formal authority (3) Personal Model (4) facilitator and (5) delegator.